Living The Spiritual Exercises: As a Married Couple and in the Christian Life Community - Gardner, Chris (The way, 2025)
The article focuses on how a married couple has integrated the Spiritual Exercises of St Ignatius into their personal and communal life through their involvement in the Christian Life Community. Topics include the transformative role of Ignatian spirituality in marriage and family life, the importance of discernment and hospitality in daily practice, and their commitment to social and spiritual priorities such as environmental care and solidarity with the marginalized.